REPRESENTATION OF ISLAM IN THE 2019 PRESIDENTIAL ELECTION DISCOURSE ON SOCIAL MEDIA - Fahmi, Muhammad (Indonesian Journal of Interdisciplinary Islamic Studies (IJIIS), 2020)
This study aims to see how religious discourse in the presidential election is represented in social media. The study concludes as follows: First: Presidential Election 2109 represents three discourses namely: Discourse on Religion and Candidacy of Candidates, Discourse on Politics and Badar War and Discourse on Ulama and Power. Second: Factors that influence representation are: political factors, religious interpretations and digital culture. On political factors, it appears that religion is politicized in the 2019 Presidential Election because religion alone provides political benefits. So for political purposes the power of religious politicization in the 2019 Presidential Election becomes a necessity. Meanwhile, on the factor of religious interpretation, it was concluded that religious interpretation influenced the representation of the 2019 Presidential Election discourse. Religious interpretation was used as a legitimate tool to support or reject certain candidates. Likewise with the digital world, the representation of religious discourse can be so massive, precisely because it is influenced by digital culture that has touched all aspects of human life, including religion. Through the digital world of marketing and the 2019 Presidential Election campaign can be faster, cheaper and more effective even though it has raised concerns over the future and integration of the Unitary Republic of Indonesia. The open nature of the digital world makes open conflict so that it has the potential to trigger national divisions.